2011
DOI: 10.1002/mop.26565
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a monopole and a PIFA handset antenna in the presence of the human head

Abstract: We reascertained a family in which first cousins were affected by Angelman syndrome and Prader–Willi syndrome. A paracentric inversion of 15q11‐q15 had previously been reported in this family but we show, using fluorescence in situ hybridization (FISH), that the rearrangement segregating in this family is not a paracentric inversion but an inverted intrachromosomal insertion, inv ins(15)(q15q13q11.2). We also describe a further recombinant resulting in a maternal duplication of the Prader–Willi/Angelman critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A dual band (GSM 900 MHz and 1800 MHz) planer inverted F-antenna (PIFA) [14,15] with circuit board was used in our simulations. The antenna design was collected from a build-in project of CST MWS Studio 2013.…”
Section: A Antenna and Circuit Boardmentioning
confidence: 99%
“…A dual band (GSM 900 MHz and 1800 MHz) planer inverted F-antenna (PIFA) [14,15] with circuit board was used in our simulations. The antenna design was collected from a build-in project of CST MWS Studio 2013.…”
Section: A Antenna and Circuit Boardmentioning
confidence: 99%
“…This does not allow the evaluation of power absorbed by different parts of the body, since SAR results give information about maximum absorption averaged over 10 g. The power absorbed in tissues (Eq. 2) was found to be the best parameter for measuring total absorption in parts of the body [Risco et al, 2012]. We demonstrated that two similar values of SAR can be related to very different values of head absorption.…”
Section: Discussionmentioning
confidence: 66%
“…The power absorbed in human tissues is another key aspect of interest, as transmitters operate in close proximity to the body. Evaluation of the specific absorption rate (SAR) is crucial for compliance with safety levels assigned by international standards [ICNIRP, ; IEEE, ], and is often investigated [Anguera et al, ; De Santis et al, ; Risco et al, ; Soh et al, ]. Designing efficient antennas while maintaining a low SAR is one of the challenges in body area networks.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Conventionally, an intensive simulation is required to optimize the antenna structure. [17,18,20] In contrast, SOA allows continuous real-time scanning of various designs to obtain the optimal antenna structure, which can be actively optimized according to the body part (e.g., hand, wrist, chest) and user characteristics.…”
Section: In Situ and In Operando Adaptationmentioning
confidence: 99%